The State of the Problem of Achieving Extremely Low LDL Levels - Korneva, Victoria; Kuznetsova, Tatiana; Julius, Ulrich (Current Pharmaceutical Design, 2021)
Patients who have achieved very low low-density lipoprotein CH (LDL-C) levels in clinical trials have shown the lowest cardio-vascular risk. The current clinical guidelines set such a concentration for LDL-C as < 1.4 mmol/L. However, the question of minimum permissible target values of the lipids remains unresolved. A number of experimental and clinical studies showed some unfavorable consequences of low LDL-C levels At the same time, the modern arsenal of lipid lowering drugs allows reducing LDL-C levels to extremely low values. This review presents an analysis of literature about the safety of low lipid spectrum parameters.
Keywords: diabetes mellitus